ANALISIS METODE THAWAB WA ‘IQOB DALAM PEMBELAJARAN BAHASA ARAB: PERSPEKTIF HADIST NABI SAW - Rahma Azizatun Ni'mah; Agung Setiyawan; Mahmudi (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2024)
This study aims to comprehensively determine the thawab wa iqob method in learning Arabic: The perspective of the hadith of the Prophet SAW. This research is a library research, where the data comes from written materials such as books, journals and so on. In collecting data, the author uses data obtained by using the documentation method taken from learning method books, Arabic learning books, Islamic education books and other supporting books. The results of the study show that the thawab method in learning Arabic is in the form of praise, as exemplified by the Prophet when he gave praise to Abu Hurairah who was enthusiastic about asking and collecting hadiths from the Prophet. In learning Arabic, teachers can apply the thawab method in the form of praise when they see good and commendable signs made by students so that when given praise, students can be more motivated and enthusiastic in the learning process. The Iqob method in learning Arabic from a hadith perspective, namely, in the form of a reprimand, the Prophet once reprimanded a friend who made a mistake in front of other friends in a gentle way so that he would not feel offended and feel ashamed. In learning Arabic, teachers can apply verbal punishment in the form of reprimands to students who commit violations or mistakes as exemplified by the Prophet, so that students are aware and do not repeat their mistakes.